Peran Pemerintah Dalam Mendorong Tindakan Kolaboratif Pengurangan Penggunaan Kantong Plastik di Kabupaten Karawang - Giesayla Febiazkana D.P; Usep Dayat; Gun Gun Gumilar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the role of Karawang Regency Government in encouraging collaborative action on the implementation of Karawang Regent Regulation Number 22 of 2021 concerning Reduction of Plastic Bags. The approach used is qualitatively descriptive with Emerson and Nabatchi's 2015 Collaborative Governance theory, with a focus on collaborative action dimensions. The data was collected through in-depth interviews with the Regional Apparatus Organization (OPD), business actors, environmental communities, and communities, as well as through documentation studies and field observations. Research results show that collaborative action has emerged in the form of socialization by local governments and education by environmental activists. However, this collaboration has not been strategic, unified, and has not touched the main target group evenly. Many business actors and the public are not aware of the existence of the regulation, which shows weak communication across sectors. Actions taken are more formal and not accompanied by participatory feedback mechanisms. This study concluded that collaborative efforts in policy implementation still need to be strengthened, both in terms of inclusion, sustainability of participation, and cross-sectoral strategy design. In this case, the local government needs to form a collaboration forum across actors to organize a more adaptive joint program and reach policy targets directly.